The motivation of french colour idioms - Negro Alousque, Isabel (Epos : Revista de filología, 2010)
The use of figurative language is not limited to poetry but rather pervades everyday speech. Figurative language has been a central research subject in the last years which has been approached from different perspectives: psychological, cognitive and linguistic. The present contribution paper focuses on a central set of figurative expressions, colour idioms, in the French language. The study concerns the different types of motivation (metaphoric or cultural) underlying French colour idioms.